2016
DOI: 10.1007/s00167-016-4259-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of ACL and anterolateral ligament. Part I: Combined lesion

Abstract: The ALL plays a significant role in controlling static internal rotation and acceleration during PS test. On the other hand, ALL resection did not produce any significant change in terms of anterior displacement. A trend was seen for the internal rotation during the pivot-shift test to increase after ALL resection was higher when compared to the intact and isolated ACL lesion states; however, the differences were not significant. The results highlight the clinical relevance of this structure that should be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 30 publications
1
56
0
9
Order By: Relevance
“…Despite recent improvements in surgical methods and understanding of ACL anatomy, it has been suggested that the normal rotational stability of the knee is not fully restored by reconstructive methods for ACL injuries [5,6]. Such abnormal biomechanics have led surgeons to focus more on anterolateral structures and, in the past few years, the ALL of the knee has been studied with regard to its anatomy and biomechanics [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent improvements in surgical methods and understanding of ACL anatomy, it has been suggested that the normal rotational stability of the knee is not fully restored by reconstructive methods for ACL injuries [5,6]. Such abnormal biomechanics have led surgeons to focus more on anterolateral structures and, in the past few years, the ALL of the knee has been studied with regard to its anatomy and biomechanics [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…47,19,31,37,45 These discrepant anatomic findings are further magnified when we consider biomechanical studies of the ALL. While some study groups found this ligament to be an important restraint of internal tibial rotation, 1,26,27,30 others described the biomechanical role of the ALL to be negligible. 20,32,43 Considering the inconsistent terms and conflicting findings, it is crucial that the anterolateral knee structure is clearly defined and a consistent terminology is developed.…”
mentioning
confidence: 99%
“…Recent studies have further investigated the anatomy of the so called "antero-lateral ligament" (ALL) (7)(8)(9), that has been clearly identified as a distinct ligamentous structure in 83 to 100% of knees. Moreover, the role of the anterolateral structures in rotational control of the knee has been demonstrated recently by several robotic cadaveric studies where the effect of a lesion of the ALL-in addition to an ACL injury was evaluated (10). Despite this, the precise role of the ALL in eliminating the pivot shift remains controversial (11).…”
Section: Abstract Acl; Antero-lateral Ligament; Navigation; Pivot-shiftmentioning
confidence: 99%
“…ALL in a cadaveric model and the same navigation system of the present study and they concluded that lesion of the ALL in an ACL deficient knee significantly increases tibial rotation and is correlated to the clinical appearance of an explosive pivot-shift in most cases. Bonazinga et al (10) evaluated the effect of progressive lesions of ACL and ALL during pivot-shift test. They specifically evaluated acceleration during the pivot shift test.…”
Section: Navigator Evaluationmentioning
confidence: 99%